PENGARUH EKSTRAK AKAR TUBA Derris elliptica Benth. TERHADAP MORTALITAS Pomacea Canaliculata Lamarck. (MESOGASTROPODA: AMPULLARIIDAE) PADA PADI Oryza sativa L. - Valentino Valentino; Burhanuddin Nasir; Moh. Hibban Toana (Universitas Tadulako, 2020)
The purpose of this study was to determine the effective concentration of tuba Derris elliptica Bent. root extract against P. canaliculata mortality, intensity of rice damages and its effect on rice production. This research was carried out in November 2013 in irrigated paddy field of Astina Village, Torue District, Parigi Moutong Regency. This study used a randomized block design consisting of six treatments of tuba root extract concentrations i.e. control, 1.25%, 2.5%, 5%, 10%, and 20%. The most effective results were shown by the tuba root extract at 10% concentration. It increased P. canaliculata mortality rate to 5.0 (2.34%), reduced the intensity of the rice tillers damages to only 3.67 (2.04%) and augmented the rice production to 5 tons/ha with an average difference between treatment was 0.2 tons/ha. These results suggest that the root extract of Derris elliptica is highly potential to be developed as botanical pesticide. Keywords : Derris elliptica Extracts, Oryza sativa L. and Pomacea. Canaliculata Lamarck.